Pengaruh Komik Strip Bermuatan Kearifan Lokal Terhadap Kemampuan Menulis Puisi Siswa SMA - Aldi Dwi Saputra; Fajar Nur Annisa; Iqbal Syahrul Akbar Al Aziz; Shalman Al Farisy Lubis; Sumarwati (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
The Effect of Comic Setrips Containing Local Wisdom on High School Students' Poetry Writing Ability. This study aims to examine the effect of comic strip media containing local wisdom on the ability to write poetry in class X SMA students. This research is a quasi-experimental research using pretest and posttest control. The research was conducted at SMA Negeri 1 Kota Binjai involving two classes, namely the experimental class and the control class. Data was collected using a performance test to measure students' ability to write poetry of local wisdom. Data analysis using T-test technique. The results showed that the average of the experimental group reached an average value of 81.73. The result of the effect is 0.91 which is a large effect.